1996
DOI: 10.1038/bjc.1996.322
|View full text |Cite
|
Sign up to set email alerts
|

K-ras mutations and HLA-DR expression in large bowel adenomas

Abstract: Summary A total of 72 sporadic colorectal adenomas in 56 patients were studied for the presence of point mutations in codons 12 and 13 of the K-ras gene and for HLA-DR antigen expression related to clinicopathological variables. Forty K-ras mutations in 39 adenomas were found (54%): 31 (77%) in codon 12 and nine (23%) in codon 13. There was a strong relationship between the incidence of K-ras mutations and adenoma type, degree of dysplasia and sex. The highest frequency of K-ras mutations was seen in large a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 41 publications
1
15
1
Order By: Relevance
“…In addition, individuals with rectal adenomas were twice as likely to have Ki-ras mutations compared with those with distal colonic adenomas ( Table 2). Univariate analyses of the relationships among adenoma size, degree of dysplasia, histology, and Ki-ras mutation showed positive associations with point estimates similar to those reported in the literature (15)(16)(17)(18)(44)(45)(46)(47)(48)(49)(50)(51). However, because these characteristics are highly correlated, multivariate analysis was required to assess the independent effect of each and showed that the presence of tubulovillous histology (OR, 4.19; 95% CI, 2.62-6.68) or of villous histology (OR, 5.45; 95% CI, 2.28-13.03) was strongly related to Ki-ras mutation as compared with tubular adenomas.…”
Section: Resultssupporting
confidence: 59%
“…In addition, individuals with rectal adenomas were twice as likely to have Ki-ras mutations compared with those with distal colonic adenomas ( Table 2). Univariate analyses of the relationships among adenoma size, degree of dysplasia, histology, and Ki-ras mutation showed positive associations with point estimates similar to those reported in the literature (15)(16)(17)(18)(44)(45)(46)(47)(48)(49)(50)(51). However, because these characteristics are highly correlated, multivariate analysis was required to assess the independent effect of each and showed that the presence of tubulovillous histology (OR, 4.19; 95% CI, 2.62-6.68) or of villous histology (OR, 5.45; 95% CI, 2.28-13.03) was strongly related to Ki-ras mutation as compared with tubular adenomas.…”
Section: Resultssupporting
confidence: 59%
“…Enriched PCR was used to obtain mutant DNA template. 25 If a mutant product was revealed by restriction analysis, the specific mutation was identified by direct sequencing using an Applied Biosystems (Rotterdam, the Netherlands) 373 DNA sequencer.…”
Section: Dna Extraction and K-ras Mutation Analysismentioning
confidence: 99%
“…In the development of sporadic CRC, K-ras mutations occur early and with high incidence (30 -60%) in the multistep process of colorectal carcinogenesis (12). Hot spots for mutations in codons 12, 13, and 61 of the K-ras gene can be used for convenient detection of tumor cells (13,14). A relation between the presence of K-ras mutations in the primary tumor and a poor prognosis has been shown by some studies (15)(16)(17)(18)(19)(20), but not by others (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Schimanski et al (24) investigated K-ras mutations in liver biopsies of patients at various CRC stages. A modified PCR-RFLP assay was used for detection, which had been originally established by Norheim-Andersen et al (14). With this method a third of all patients with K-ras mutated primary tumors were found to harbor ITCs showing K-ras mutation in the liver identical to the primary tumor (24).…”
Section: Introductionmentioning
confidence: 99%